Effect of mind mapping combined with the SBAR shift turnover model on reducing nursing defects during bedside shift turnovers after cardiac stenting in cardiology - Che, Sujuan; Chen, Fangfang; Liu, Jingjing; Wang, Jie; Miao, Rongrong (Frontiers in Surgery, 2026)
AimThis study aims to explore the effect of a mind mapping technique combined with the situation–background–assessment–recommendation (SBAR) shift turnover model on reducing nursing defects during bedside shift turnovers after cardiac stenting in cardiology.MethodsThis quasi-experimental study retrospectively analyzed clinical data of 96 patients who received cardiac stenting at our hospital between August 2022 and August 2023. According to the time of admission, patients were divided into an observation group (OG, n = 48) and a control group (CG, n = 48). Fourteen nurses participated in the study; they were matched by professional level and then randomly assigned to the OG and CG (n = 7 per group). The CG adopted the traditional mode of shift turnover. Based on the CG approach, the OG adopted a mind map combined with the SBAR shift turnover model. Outcomes compared between the two groups included the quality of shift turnover, nurses’ mastery of patient condition, handover time, defect rate of shift turnover, incidence of nursing adverse events and complaints, and patient satisfaction.ResultsCompared with the CG, the OG showed higher scores for shift turnover quality and nurses’ mastery of patient conditions, shorter handover time, and higher patient satisfaction (P < 0.05). The defect rate of shift turnover and the incidence of nursing adverse events and complaints were lower in the OG; however, these differences were not statistically significant.ConclusionIn this single-center study, integrating a mind map-supported SBAR handover into bedside shift handovers was associated with shorter handover time, fewer observed handover defects, and higher patient satisfaction. These findings suggest potential clinical benefits for communication safety after cardiac stenting; however, the results should be interpreted cautiously due to the small nurse-level sample size and study design.